EXPERIMENTAL CONSTRAINTS ON HIGH PRESSURE MELTING IN SUBDUCTED CRUST - Hermann J.; Green D.H. (My University, 2001)
Synthesis piston-cylinder experiments were carried out from 2.0 to 4.5 GPa and 850 to 1150°C in order to determine phase and melting relations in a model composition for subducted crust (K2O–CaO–MgO–Al2O3-SiO2–H2O). As subduction zone magmas are enriched in H2O and large ion lithophile elements (LILE), this study concentrates on the stability of phases that host these elements. Biotite and phengite were found to be the stable phases able to transport H2O and LILE to mantle depths. At pressures below 3.0 GPa biotite is stable to higher temperatures than phengite and melting related to biotite breakdown occurs at about 950°C. At higher pressure, only phengite melting occurs along the reaction phengite+clinopyroxene+coesite→garnet+kyanite+melt+K-feldspar, which has a positive slope to 1050°C, 4.5 GPa. Biotite reacts to phengite under subsolidus conditions with the conservation of LILE and H2O stored in the rock. The stability of phengite to high pressures and temperatures prevents liberation of LILE and H2O by ‘fluid absent’ melting in subduction zones with a normal thermal gradient. It is suggested that these elements are probably released by melting in the presence of fluids, which derive from dehydration of the mafic or ultra-mafic layer of the slab. The experiments demonstrate that melts produced by mica melting or by addition of small amounts of H2O at lower temperatures are granitic in composition and display an increase of K2O with increasing temperature. Determination of trace element partitioning between melt and residue indicates that the heavy rare earth elements will be incorporated in garnet and strongly enriched in the residue whereas the LILE preferentially enter the melt even if there is phengite in the residue. The light rare earth elements (LREE) are not significantly enriched in the granitic melts because of small amounts of LREE-rich allanite in the residue. Such hydrous granitic melts could participate in the metasomatism of the mantle wedge and might be partly responsible for the characteristic trace element patterns of subduction zone magmas.
Keywords: experimental studies; partial melting; subduction; phengite; trace elements; crust